Comparison of antibiotic resistance and virulence in vancomycin-susceptible and vancomycin-resistant Enterococcus faecium strains - Sieńko, Anna; Czaban, Sławomir; Ojdana, Dominika; Majewski, Piotr; Wieczorek, Anna; Sacha, Paweł; Tryniszewska, Elżbieta Anna; Wieczorek, Piotr (Journal of Medical Science, 2018)
Aim. Today, infections caused by vancomycin-resistant Enterococcus faecium (VRE) are a major problem in the healthcare system. The aim of this study was to compare the antibiotic resistance and virulence traits between vancomycin-susceptible E. faecium (VSE) and VRE clinical isolates.Material and Methods. Studies were performed on 66 E. faecium (32 VRE and 34 VSE) strains. Susceptibility testing and identification were performed, and strains were examined for ß-lactamase, hemolysin and biofilm production. Isolates were tested for the presence of 5 van genes, 8 virulence genes and 6 aminoglycoside-modifying enzyme (AME) genes. Obtained amplicons were subjected to electrophoretical separation and DNA sequencing.Results. Among 32 VRE isolates, 28 were found to have the VanA phenotype, and 4 the VanB. The most frequent resistance and virulence profile among VRE strains was resistance to ampicillin, imipenem, gentamicin, streptomycin, teicoplanin, and vancomycin with enterococcal surface protein (esp), endocarditis antigen (efaA), collagen adhesin (acm), and hialuronidase (hyl) genes; among VSE: resistance to ampicillin, imipenem, gentamicin, streptomycin with esp, efaA, acm, and hyl genes. Conclusions. Our findings prove that both VRE and VSE strains were well equipped with virulence and resistance genes, although VRE strains were characterized by a greater variety and a higher number of these genes. However, statistical analysis revealed no significant differences between VSE and VRE strains (p > 0.05). Nevertheless, our results suggest that VRE strains may slowly acquire and incorporate resistance and virulence genes, due to their ability to survive in a hospital environment for a long time.